EFEKTIVITAS UNIT PENGUMPUL ZAKAT KUA DALAM MENGEDUKASI MASYARAKAT MAIWA TERKAIT KEWAJIBAN ZAKAT PERTANIAN - Andi Marlian; Usman; Rini Purnama Sari; Muhammad Al Jazary (Indonesia Journal of Zakat and Waqf, 2024)
This study examines the role of the Zakat Collection Unit (UPZ) of KUA Maiwa in raising the awareness of the farming community towards the obligation of agricultural zakat amidst the low level of awareness, especially regarding agricultural zakat, although the potential for zakat from the agricultural sector in the Maiwa area, Enrekang Regency, is very large. This low awareness is influenced by the lack of public understanding of agricultural zakat and the limited socialization conducted by UPZ KUA Maiwa, plus the challenges in gathering farmer groups for socialization. Qualitative methods through observation, interviews, and documentation were used to understand the role of UPZ KUA in raising community awareness. The results revealed that the level of awareness of the Maiwa community in paying agricultural zakat is still very low, caused by the lack of understanding and effectiveness of socialization. UPZ KUA Maiwa faces significant challenges in carrying out the socialization of agricultural zakat, including the lack of participation of farmers and the existence of misconceptions among the community regarding zakat. Therefore, this study concludes that there is a need for a more intensive socialization strategy and involving various elements of society to increase public awareness and compliance in paying agricultural zakat, so that the potential of zakat can be optimized for common welfare.